Ecological Efficiency” as a Value Criterion of the Sustainable Development Strategy - Gunzenova, Karina (European Journal of Sustainable Development, 2019)
The current legal frameworks of the Russian Federation, which intermediate socio-natural relations, may contradict the course set towards sustainable development due to their dependence on the formerly dominant technocratic view of the world leading to various systemic destructions. Not always do the quantitative indicators contribute to finding the best way of environmental-economic development. In this connection, the issue of a high-quality assessment of the effectiveness of strategies, plans, and other regulatory and legal documents in achieving sustainable development goals is analyzed. This paper considers the “ecological efficiency” assessment of the legislation as a value criterion measuring the relevance of the planning and strategic documents to the essence of sustainable development. The paper aims to expose the essence of the “ecological efficiency” concept and its role in the harmonization mechanism for socio-natural relationships. The dialectical method, which determines interconnections between the values existing earlier and the character of socio-natural development on the one hand, and the emerging environmental ethics-based comprehensive worldview and sustainable development on the other, was used as the primary research instrument. Research results showed the existing potential for the use of “ecological efficiency” as a value criterion to assess the relevance of state plans and strategies to the declared sustainable development goals. “Ecological efficiency” helps to resolve the current contradictions in social development management thus contributing to the formation of the sustainable development legislation relevant to the level of public consciousness and behavior. Keywords: ecological efficiency, strategic development, sustainable development legislation, sociocultural development factor.